Customer experiences in the age of artificial intelligence. (January 2021) - Ameen, Nisreen; Tarhini, Ali; Reppel, Alexander; Anand, Amitabh
Abstract: Artificial intelligence (AI) is revolutionising the way customers interact with brands. There is a lack of empirical research into AI-enabled customer experiences. Hence, this study aims to analyse how the integration of AI in shopping can lead to an improved AI-enabled customer experience. We propose a theoretical model drawing on the trust-commitment theory and service quality model. An online survey was distributed to customers who have used an AI- enabled service offered by a beauty brand. A total of 434 responses were analysed using partial least squares-structural equation modelling. The findings indicate the significant role of trust and perceived sacrifice as factors mediating the effects of perceived convenience, personalisation and AI-enabled service quality. The findings also reveal the significant effect of relationship commitment on AI-enabled customer experience. This study contributes to the existing literature by revealing the mediating effects of trust and perceived sacrifice and the direct effect of relationship commitment on AI-enabled customer experience. In addition, the study has practical implications for retailers deploying AI in services offered to their customers. Highlights: Artificial intelligence (AI) is changing customer experiences. The study develops a model drawing on trust-commitment theory and service quality model. Trust and perceived sacrifice play significant mediating role. Relationship commitment has a significant effect on AI-enabled customer experience. Perceived convenience and personalisation play a significant role in AI-enabled experiences.